Method for producing lithium sulfide
By using a combination method of carbon element reducing agent and reducing gas in the lithium sulfide manufacturing process, combined with the crushing and drying process, the problem that lithium sulfide in the prior art is difficult to achieve high purity, and high efficiency and low impurity lithium sulfide is achieved Preparation, suitable for the production of solid electrolytes.
Patent Information
- Application Number
- CN202180044404.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-07-09
- Filing Date
- 2021-07-02
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2041-07-02
AI Technical Summary
The prior art is difficult to achieve high purity when manufacturing lithium sulfide. Using a large amount of carbon material as a reducing agent will produce the by-product lithium carbonate. The use of reducing gas will lead to a decrease in the reaction heat and specific surface area, which will inhibit reactivity.
Using a combination of a reducing agent containing carbon elements and a reducing gas, the raw materials of lithium and sulfur are first reduced by a reducing agent of carbon elements to obtain intermediate products, and then further reducing gas is used to combine the crushing and drying process to improve the Reaction efficiency.
The manufacturing of high-purity lithium sulfide is achieved, the impurity content is reduced, the purity and reaction efficiency of lithium sulfide are improved, and it is suitable as a raw material for solid electrolytes.
Smart Images

Figure BDA0004010383130000201 
Figure BDA0004010383130000211
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing lithium sulfide. Background Art
[0002] As a method for producing lithium sulfide, for example, a method of reducing lithium sulfate is known. For example, Patent Document 1 describes a method comprising the following steps: a step of finely dividing a powder containing lithium sulfate into fine particles having a specific particle size; and a step of reducing the fine particles with carbon black to obtain lithium sulfide.
[0003] Patent Document 2 describes a method comprising: a step of reducing lithium sulfate to generate lithium sulfide by heating a mixture containing lithium sulfate and graphite powder and bringing the mixture into contact with a carbon formed body; and a step of separating the generated lithium sulfide from the carbon formed body. In the step of generating lithium sulfide, both the carbon material and the carbon formed body are used as reducing agents for lithium sulfate.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2013-227180
[0007] Patent Document 2: Japanese Patent Application Publication No. 2015-74567 Summary of the invention
[0008] As the reducing agent used when producing lithium sulfide, for example, there can be mentioned the carbon materials described in Patent Documents 1 and 2. In addition, a reducing gas may be used as the reducing agent.
[0009] In addition, when manufacturing lithium sulfide, it is required to obtain lithium sulfide of higher purity. As a method for obtaining high-purity lithium sulfide, a method of using a large amount of reducing agent to fully reduce lithium sulfate is considered. However, if a large amount of carbon material is used as a reducing agent, lithium carbonate is produced as a by-product as an impurity, and as a result, high-purity lithium sulfide cannot be obtained. In addition, when a large amount of reducing gas is used as a reducing agent, reaction heat is generated, resulting in the melting of lithium sulfate and a significant decrease in specific surface area. This inhibits the contact between lithium sulfate and reducing gas, resulting in a decrease in reactivity.
[0010] Therefore, an object of the present invention is to provide a method capable of producing high-purity lithium sulfide.
[0011] The present inventors have conducted intensive studies to solve the above-mentioned problems and have found that high-purity lithium sulfide can be produced by using a carbon-containing substance and a reducing gas in combination as a reducing agent.
[0012] The present invention is made based on the above discovery and provides a method for producing lithium sulfide, which comprises:
[0013] A first step of reducing a raw material containing lithium (Li) and sulfur (S) using a reducing agent containing carbon (C) to obtain an intermediate product; and
[0014] The second step is to reduce the intermediate product using a reducing gas to obtain lithium sulfide.
[0015] The present invention also provides a method for producing lithium sulfide, comprising the step of reducing a raw material containing lithium (Li) element and sulfur (S) element using a reducing agent containing carbon (C) and a reducing gas to obtain lithium sulfide.
[0016] Furthermore, the present invention provides a method for producing a solid electrolyte, comprising:
[0017] Step A for obtaining lithium sulfide;
[0018] Step B of mixing the lithium sulfide, phosphorus pentasulfide and lithium halide to obtain a raw material composition; and
[0019] Step C of calcining the raw material composition,
[0020] The above-mentioned step A includes: a first step of reducing a raw material containing lithium (Li) element and sulfur (S) element using a reducing agent containing carbon (C) element to obtain an intermediate product; and a second step of reducing the above-mentioned intermediate product using a reducing gas to obtain lithium sulfide. DETAILED DESCRIPTION
[0021] The present invention is described below based on a preferred embodiment of the present invention. The present invention relates to a method for producing lithium sulfide (Li2S). In the present invention, a raw material containing lithium (Li) element and sulfur (S) element is used as a raw material for producing lithium sulfide. The raw material is reduced to obtain an intermediate product (hereinafter referred to as the "first step"), and then the intermediate product is reduced (hereinafter referred to as the "second step") to obtain the target lithium sulfide. These steps are described in detail below.
[0022] As the aforementioned raw material used in the first step, compounds containing lithium (Li) element and sulfur (S) element can be preferably cited. Examples of such compounds include lithium sulfate (Li2SO4), lithium sulfite (Li2SO3), lithium thiosulfate (Li2S2O3), etc. These compounds can be used alone, or two or more can be used in combination. From the viewpoint of industrial availability and ease of handling, lithium sulfate is preferably used as a raw material. Lithium sulfate is usually supplied to the first step in a solid state such as powder or granules. Lithium sulfate is usually a hydrous salt, but in the present invention, a hydrous salt of lithium sulfate can be used directly, or a hydrous salt of lithium sulfate can be dehydrated and used in the state of anhydrous salt.
[0023] In the first step, the raw material is reduced by a reducing agent to obtain the target lithium sulfide intermediate product. From the perspective of easily obtaining high-purity lithium sulfate, the reducing agent used in this step is preferably a reducing agent containing carbon (C) element. "Reducing agent containing carbon (C) element" refers to a substance that has a reducing power capable of reducing the raw material and contains carbon (C) element as a constituent element.
[0024] As a reducing agent containing carbon (C) element, there is no particular limitation as long as it is a substance commonly used as a carbon-based reducing agent, and it can be a gas, a liquid, or a solid. As long as the aforementioned reducing agent can be a reducing agent that can become a source of carbon supply, it can contain non-carbon atoms. As such a reducing agent, organic compounds such as monohydric alcohols, polyhydric alcohols, and reducing sugars represented by glucose can be listed. In addition, solid carbonaceous materials such as coal, coke, graphite, carbon black, fullerene, carbon tubes, charcoal, carbide, and elemental carbon and its allotropes can also be listed. As elemental carbon and its allotropes, graphite can be listed as a typical example. In the present invention, from the viewpoint of reducing ability, it is preferred to use charcoal, bamboo charcoal, activated carbon and other carbon, carbon black, and activated carbon is particularly preferred. Activated carbon can be powdered activated carbon or granular activated carbon. It should be noted that as a reducing agent containing carbon element, one of the above materials can be used, or two or more can be used in combination.
[0025] The shape of the reducing agent containing carbon element is not particularly limited, and it can be, for example, fibrous, granular, or powdery. The average particle size of the granular reducing agent can be, for example, less than 1000 μm, less than 300 μm, or less than 150 μm. On the other hand, the average particle size of the reducing agent can be, for example, greater than 0.1 μm, greater than 1 μm, or greater than 10 μm. The smaller the average particle size of the reducing agent, the greater the contact area when mixed with the raw material, so that reduction can be performed more efficiently. The average particle size referred to here is the volume cumulative particle size D at a cumulative volume of 50% by volume based on the laser diffraction scattering particle size distribution measurement method. 50.
[0026] The first step is preferably a step of mixing the raw material and the reducing agent and reducing the raw material using the reducing agent. When the reducing agent is solid, the reaction between the reducing agent and the raw material becomes a solid phase reaction, so the reducing agent is provided to the reduction reaction in a state of being fully mixed with each other, which is preferred from the viewpoint of being able to efficiently reduce the raw material.
[0027] As a mixer used in mixing, for example, a mixer can be used that mixes by moving a container filled with the raw materials and the reducing agent for mixing. Alternatively, a mixer can be used that mixes the raw materials and the reducing agent by rotating a rotating body of a plate, screw, ribbon, cylinder, disk, or any other shape provided in a container filled with the raw materials and the reducing agent. Alternatively, a mixer of the following type can be used: a pulverizing medium such as balls and beads made of ceramic, glass, metal, resin, or other materials is filled into a container filled with the raw materials and the reducing agent together with the raw materials and the reducing agent, a force is applied to the medium, and the two are mixed by the movement of the medium.
[0028] As a dispersion medium used to form a dispersed state of the raw material and the reducing agent during mixing, a gas such as air (so-called dry method) can be used. Alternatively, a liquid such as water or an organic solvent (so-called wet method) can be used. Alternatively, the mixing of the raw material and the reducing agent can be performed under vacuum.
[0029] When a liquid is used as a dispersion medium, a liquid that does not dissolve the aforementioned raw materials may be used, or a liquid that dissolves the aforementioned raw materials may be used. In addition, when a liquid is used as a dispersion medium, drying may be performed after mixing to remove the liquid.
[0030] The first step is preferably a step of reducing after crushing at least one of the raw material and the reducing agent. "Crushing at least one of the raw material and the reducing agent" means that only the raw material can be crushed, or only the reducing agent can be crushed. It is particularly preferred to crush both the raw material and the reducing agent. The reason is that the raw material can be efficiently reduced because the contact area between the raw material and the reducing agent can be made larger. In the case of crushing both the raw material and the reducing agent, the raw material and the reducing agent can be crushed separately, or the mixture formed by mixing the raw material and the reducing agent can be crushed. The latter is particularly preferred because the process becomes simple, economically advantageous, and more efficient reduction can be achieved.
[0031] As a method for pulverizing at least one of the raw material and the reducing agent, wet pulverization or dry pulverization can be cited. The dispersion medium used in the wet pulverization is not particularly limited, and water is preferred, for example. Using water as the dispersion medium is economically preferred.
[0032] When the raw material is a water-soluble raw material, for example, the raw material and the reducing agent are mixed and wet-pulverized to form a suspension in which the reducing agent is suspended in a raw material solution in which at least a part of the raw material is dissolved.
[0033] When wet pulverization is performed, in order to remove the dispersion medium as needed, it is preferred to dry the turbid liquid to which the dispersion medium has been added. For example, when the raw material and the reducing agent are mixed and wet pulverized, by drying after wet pulverization, a mixture with the raw material attached is obtained in a manner that the raw material is precipitated on the surface of the reducing agent and the reducing agent is coated around the reducing agent. Thus, compared with the case where the powders of the raw material and the reducing agent are simply mixed, a state in which the raw material and the reducing agent are in closer contact is formed, forming a more preferred state for solid phase reaction. In addition, when both the mixing step and the pulverizing step are performed in a wet manner, the method of providing a drying step after performing the two steps continuously or simultaneously in a wet manner enables only one drying step to be performed, and is therefore economically preferred.
[0034] In the first step, the reduction reaction can be carried out under non-heating or under heating depending on the types of the raw materials and the reducing agent. In the case of the reduction reaction under heating, from the viewpoint of effectively carrying out the reduction reaction, as a temperature condition, the temperature in the system is preferably set to 700° C. or more and 850° C. or less, more preferably 720° C. or more and 830° C. or less, and more preferably 750° C. or more and 800° C. or less. At this time, from the viewpoint of effectively carrying out the reduction reaction, the heating time is preferably set to 0.5 hours or more and 6 hours or less, and more preferably 1 hour or more and 3 hours or less.
[0035] The atmosphere during the reduction reaction may be a reducing atmosphere or a non-reducing atmosphere. In the present invention, from the viewpoint of obtaining lithium sulfide of higher purity, the first step is preferably performed in a non-reducing atmosphere.
[0036] As reducing atmosphere, for example, hydrogen atmosphere, hydrogen atmosphere diluted with inert gas, etc. can be mentioned. On the other hand, as non-reducing atmosphere, for example, inert gas atmospheres such as nitrogen atmosphere and argon atmosphere can be mentioned. It should be noted that when using a reducing atmosphere as the atmosphere for performing the reduction reaction, the first step and the second step described later can be performed simultaneously, or the second step can be performed separately after the first step. When the first step and the second step are performed simultaneously, it is preferred to appropriately adjust the concentration of the reducing gas, the reaction temperature of the raw material and the aforementioned gas, and the reaction time in such a way that no reducing agent containing the carbon (C) element remains after the reaction in the first step.
[0037] In the first step, the amount of the reducing agent is preferably determined in relation to the amount of the raw material. Specifically, the amount of the reducing agent is preferably set to an amount that is substantially exactly consumed in the reaction in which all the raw materials are reduced to lithium sulfide (hereinafter referred to as "substantially equivalent"). For example, when the raw material is lithium sulfate and the reducing agent is a carbon element (such as activated carbon), the reduction reaction of lithium sulfate can be represented by the following formula (1).
[0038] Li2SO4+2C→Li2S+2CO2 (1)
[0039] In formula (1), in order to reduce 1 mole of lithium sulfate to generate 1 mole of lithium sulfide (Li2S), 2 moles of simple carbon are required, and 1 equivalent of reduction is 2 moles. From another perspective, when comparing the simple carbon as a raw material with the oxygen (O) element in the carbon dioxide as a product, it can be said that 2 moles of oxygen (O) element are consumed relative to 1 mole of carbon (C) element. Below, for convenience, the equivalent ratio of C1 mole / O2 mole (hereinafter referred to as "C / O2") shown in formula (1) is used to represent the ratio of the amount of the reducing agent used to the amount of a certain raw material. The "substantial equivalent" mentioned above is not equivalent to "C / O2 is 1" for reasons described later. When a simple carbon is used as a reducing agent in an actual reduction reaction, the reduction reaction product is not limited to carbon dioxide, and carbon monoxide is sometimes generated as shown in the following formula (2) depending on the conditions.
[0040] Li2SO4+4C→Li2S+4CO (2)
[0041] The carbon monoxide generated in the formula (2) may be directly discharged to the outside of the reaction system, or may be provided for a reduction reaction such as the formula (3).
[0042] Li2SO4+4CO→Li2S+4CO2 (3)
[0043] If formula (2) and formula (3) occur continuously, it can also be regarded as the reaction of formula (1) that occurs. In fact, the inventors believe that the reactions of formula (1), formula (2) and formula (3) occur simultaneously. In addition, at least a portion of the generated carbon monoxide will not be consumed by the reduction reaction, but will be discharged outside the reaction system. Therefore, even if the amount of the raw material and the reducing agent is adjusted in a manner such that C / O2 is 1, the amount of the reducing agent at this time is less than the substantial equivalent. The preferred C / O2 range that reaches the substantial equivalent is 0.8 or more and 1.3 or less, more preferably 0.9 or more and 1.2 or less, and more preferably 1.0 or more and 1.1 or less.
[0044] The method of using the reducing agent in the above-mentioned manner has the following advantages. That is, when the raw material is converted into the target lithium sulfide by a reduction reaction, in order to convert more raw materials into lithium sulfide, it is advantageous to use the reducing agent in a substantially equivalent amount or more. However, if a substantially equivalent amount or more reducing agent is used, although all the raw materials are reduced, unreacted reducing agent will remain in the product, and a large amount of lithium carbonate will be produced as a by-product. The presence of residual reducing agent and lithium carbonate in the product is one of the reasons for the impaired lithium ion conductivity of the sulfide solid electrolyte manufactured using lithium sulfide as a raw material. In addition, it is very difficult to adjust the ratio of the amount of raw material to the amount of reducing agent to be exactly substantially equivalent, and even if it can be adjusted to be exactly substantially equivalent, the by-production of lithium carbonate cannot be avoided. When the raw material is reduced using a carbonaceous reducing agent, it is extremely difficult to produce only lithium sulfide without by-production of lithium carbonate. Therefore, in the present invention, excessive by-production of lithium carbonate is suppressed by setting the ratio of the amount of reducing agent to the amount of raw material to be less than substantially equivalent. Of course, although the amount of the reducing agent is set to a substantial equivalent or less, it is possible to suppress excessive by-product lithium carbonate, but there is a risk of residual unreacted (i.e., unreduced) raw materials in the reaction system. Therefore, in the present invention, in the second step described later, the raw materials remaining in the reaction system are reduced and (when lithium carbonate is present in the reaction system) lithium carbonate is decomposed to obtain high-purity lithium sulfide. The decomposition reaction of the lithium carbonate can be shown in the following formula (4).
[0045] Li2CO3+H2→Li2O+CO+H2O (4)
[0046] From the viewpoint of minimizing the amount of impurities contained in lithium sulfide, which is the target product of the present production method, at the time of completion of the first step, in the X-ray diffraction pattern measured by an X-ray diffractometer of the substance existing in the system, that is, the intermediate product obtained by the first step, the intensity of the peak observed at 2θ=25.6°±0.5° is defined as I A , the intensity of the peak observed at 2θ = 27.1° ± 0.5° is defined as I B When I A Relative to I B The ratio (I A / I B ) is 0.10 or less. On this basis, in the aforementioned X-ray diffraction pattern, the intensity of the peak observed at 2θ=21.2°±0.5° is set as I C When I C Relative to I B The ratio (I C / I B ) is 0.03 or more and 0.09 or less. From the viewpoint of further reducing the amount of impurities in lithium sulfide, I A / I BThe value of is more preferably 0.05 or less. A / I B The value of is most preferably zero. On the other hand, I C / I B The value of is more preferably 0.03 or more and 0.08 or less.
[0047] The peak observed at 2θ=25.6°±0.5° is attributed to lithium sulfate. The peak observed at 2θ=27.1°±0.5° is attributed to lithium sulfide. The peak observed at 2θ=21.2°±0.5° is attributed to lithium carbonate. That is, the first step is preferably carried out in a manner that minimizes the residual amount of lithium sulfate used as one of the raw materials and makes the amount of lithium carbonate produced as a by-product within a specified range.
[0048] The first step is preferably performed by placing the raw material and the reducing agent in a container inactive to the reduction reaction. Examples of such a container include a sagger made of alumina.
[0049] An intermediate product is obtained by the reduction reaction in the first step. The intermediate product is usually a mixture containing unreacted raw materials, lithium sulfide as the target product, and by-products. The by-products vary depending on the type of raw materials. For example, when the raw material is lithium sulfate, a typical by-product is the above-mentioned lithium carbonate.
[0050] After the first step is completed, the substance (the intermediate product) present in the reaction system is supplied to the second step. An additional step may be performed between the first step and the second step as required. As the additional step, for example, a step of crushing the intermediate product obtained in the first step may be mentioned. The reaction occurring in the second step is a gas-solid reaction between the intermediate product as a solid and the reducing gas, so the contact between the intermediate product and the reducing gas can be promoted by adding a crushing step, and the reaction can be efficiently performed.
[0051] In the second step, a reducing gas is used to reduce the substance present in the reaction system after the first step. Examples of the reducing gas include hydrogen gas and hydrogen gas diluted with an inert gas. It should be noted that the second step is preferably performed in the absence of the reducing agent used in the first step. That is, when performing the second step, it is preferred that the reducing agent used in the first step is not present in the reaction system.
[0052] The pressure of the reducing gas in the reaction system may be atmospheric pressure, or may be a pressure lower than atmospheric pressure or higher than atmospheric pressure. Generally speaking, satisfactory results can be obtained by flowing the reducing gas in the reaction system at atmospheric pressure.
[0053] The reduction reaction in the second step can be carried out under non-heating or heating depending on the type of reducing gas. When the reduction reaction is carried out under heating, from the viewpoint of effectively carrying out the reduction reaction, as a temperature condition, the temperature in the system is preferably set to 830° C. or more and 930° C. or less, more preferably 830° C. or more and 900° C. or less, and more preferably 830° C. or more and 870° C. or less. At this time, from the viewpoint of effectively carrying out the reduction reaction, the heating time is preferably set to 1 hour or more and 12 hours or less, more preferably 2 hours or more and 8 hours or less, and more preferably 3 hours or more and 6 hours or less.
[0054] The second step can be performed simultaneously with the first step or after the first step. In the second step, the substance existing in the reaction system after the first step, that is, the intermediate product obtained in the first step, is reduced to further generate lithium sulfide. Specifically, in the second step, lithium sulfate as an unreacted raw material contained in the intermediate product is reduced to lithium sulfide, and lithium carbonate as a by-product is decomposed into lithium oxide. As a result, the amount of impurities contained in the final product after the second step is further reduced.
[0055] A method of reducing the raw material with a reducing gas to obtain lithium sulfide by performing only the second step without performing the first step is also considered. However, in this case, the heat of reaction is generated due to the reduction, which causes the temperature in the reaction system to rise, and sometimes exceeds the melting point of the raw material, causing the raw material to melt. The melting of the raw material will cause a significant decrease in the specific surface area, which in turn leads to a decrease in reactivity. Therefore, it is not easy to reduce the raw material using only a reducing gas.
[0056] Therefore, the present invention is the first to achieve easy production of high-purity lithium sulfide by appropriately combining the two, compared to the prior art in which lithium sulfide cannot be produced smoothly by using a reducing gas alone or a carbon-based reducing agent alone. It should be noted that in the present invention, a carbon-based reducing agent is used in the first step and a reducing gas is used in the second step, but the inventors have confirmed that the desired effect cannot be obtained by reversing the order and using a reducing gas in the first step and a carbon-based reducing agent in the second step.
[0057] In the second step, from the viewpoint of further improving the purity of the target lithium sulfide, when the substances existing in the system, that is, the lithium sulfide as the final product, are measured by an X-ray diffraction device at the end of the second step, the X-ray diffraction pattern thus obtained is C Compared with the above I B The ratio (I C / I B) is preferably 0.02 or less. On this basis, the intensity of the peak observed at 2θ=33.6°±0.5° in the aforementioned X-ray diffraction pattern is set as I D When I D Relative to I B The ratio (I D / I B ) is 0.05 or less. From the viewpoint of further reducing the amount of impurities in lithium sulfide, I C / I B The value of is more preferably 0.01 or less. C / I B The value of is most preferably zero. On the other hand, I D / I B The value of is more preferably 0.03 or less. D / I B The value of is most preferably zero. It should be noted that the peak observed at 2θ=33.6°±0.5° is attributed to lithium oxide.
[0058] The second step is preferably carried out by placing the intermediate product obtained in the first step in a container inactive to the reducing gas. Examples of such a container include a sagger made of alumina.
[0059] The target lithium sulfide is obtained through the above steps. The lithium sulfide has a low impurity content and high purity. As the main impurity, lithium oxide (Li2O) can be cited. Lithium oxide is generated by the reduction of lithium carbonate in the second step. From the viewpoint of further improving the purity of lithium sulfide, after the second step is completed, the obtained lithium sulfide can be supplied to the third step. In the third step, a reaction is carried out to convert the lithium oxide contained in the lithium sulfide obtained by the second step into lithium sulfide. For this purpose, the lithium sulfide obtained by the second step is preferably heated under a sulfur-containing gas atmosphere. Thereby, the lithium oxide contained in the lithium sulfide as an impurity is sulfurized to generate lithium sulfide.
[0060] As the sulfur-containing gas used in the third step, for example, hydrogen sulfide (H2S) gas and sulfur (S) gas can be cited. These gases can be used alone or in combination of two or more. These gases can be used directly or diluted with a rare gas. The pressure of the sulfur-containing gas in the reaction system can be atmospheric pressure, or can be a pressure lower than atmospheric pressure or higher than atmospheric pressure. Usually, sulfurization can be smoothly carried out by circulating the sulfur-containing gas in the reaction system under atmospheric pressure.
[0061] In the third step, from the viewpoint of efficiently performing the sulfidation of lithium oxide, the temperature in the system is preferably set to 200° C. to 1000° C., more preferably 300° C. to 900° C., and even more preferably 400° C. to 800° C. At this time, from the viewpoint of efficiently performing the sulfidation reaction, the heating time is preferably set to 15 minutes to 6 hours, more preferably 30 minutes to 4 hours, and even more preferably 1 hour to 3 hours.
[0062] In the third step, from the viewpoint of further improving the purity of the target lithium sulfide, it is preferred to carry out the third step in the following manner: when the substances present in the system are measured by an X-ray diffraction device at the time of completion of the third step, in the X-ray diffraction pattern obtained thereby, C Compared with the above I B The ratio (I C / I B ) is 0.02 or less. On this basis, the second step is preferably performed as follows: in the aforementioned X-ray diffraction pattern, the intensity of the peak observed at 2θ=33.6°±0.5° is set as I D When I D Relative to I B The ratio (I D / I B ) is 0.05 or less. From the viewpoint of further reducing the amount of impurities in lithium sulfide, it is further preferred that C / I B The value of is 0.01 or less. C / I B The value of is zero. On the other hand, I D / I B The value of is preferably 0.03 or less, particularly preferably 0.02 or less, and particularly preferably 0.01 or less. D / I B The value of is most preferably zero.
[0063] In the above description, the first step and the second step are performed separately in a time series, but, as an alternative to this method, the first step and the second step may be performed simultaneously. In detail, lithium sulfide may be obtained by reducing a raw material containing a lithium (Li) element and a sulfur (S) element with a reducing agent containing a carbon (C) element and a reducing gas. In this case, the types of the raw material, the reducing agent containing a carbon (C) element, and the reducing gas are the same as those described above. The pressure of the reducing gas is also the same as that described above. Furthermore, the charging ratio of the raw material and the reducing agent containing a carbon (C) element is also the same as that described above.
[0064] From the viewpoint of effectively performing the reduction reaction of the raw material, the temperature condition in the system during the reduction is preferably set to 830° C. or higher and 870° C. or lower, and more preferably set to 840° C. or higher and 860° C. or lower. At this time, from the viewpoint of effectively performing the reduction reaction, the heating time is preferably set to 1 hour or higher and 12 hours or lower, more preferably set to 2 hours or higher and 8 hours or lower, and even more preferably set to 3 hours or higher and 6 hours or lower.
[0065] The reduction under the above conditions can also obtain the target high-purity lithium sulfide. Of course, if the purity of the obtained lithium sulfide, especially the amount of lithium oxide as an impurity, is compared, the method of performing the first step and the second step separately is more excellent than this step.
[0066] After lithium sulfide is obtained in this step, the lithium sulfide can be subjected to the sulfidation step as the third step as described above. By subjecting the lithium sulfide to the third step, even if lithium sulfide contains lithium oxide as an impurity, the purity of the finally obtained lithium sulfide can be improved by sulfiding the lithium oxide.
[0067] The lithium sulfide thus obtained is suitable for use as a raw material for a solid electrolyte. The following is an explanation of the method for producing the solid electrolyte of the present invention. The method for producing the solid electrolyte of the present invention comprises: a step A for obtaining lithium sulfide; a step B for mixing the aforementioned lithium sulfide, phosphorus pentasulfide and lithium halide to obtain a raw material composition; and a step C for calcining the aforementioned raw material composition. The aforementioned step A comprises: a first step for reducing a raw material containing a lithium (Li) element and a sulfur (S) element using a reducing agent containing a carbon (C) element to obtain an intermediate product; and a second step for reducing the aforementioned intermediate product using a reducing gas to obtain lithium sulfide.
[0068] Each step will be described below. Step A can be carried out in the same manner as the above-mentioned method for producing lithium sulfide, so description thereof is omitted here.
[0069] The lithium halide used in step B can be one or more. As the lithium halide, for example, lithium chloride (LiCl), lithium bromide (LiBr) etc. can be mentioned. As the mixing in step B, for example, mechanical grinding can be mentioned. As mechanical grinding, for example, vibration mill, ball mill, turbine mill, mechanical fusion, disc mill etc. can be mentioned, among which ball mill is preferred. As long as the desired raw material composition can be obtained, the conditions of the ball mill are not particularly limited, for example, the bottom plate rotation speed is preferably more than 200rpm, particularly preferably more than 300rpm, preferably less than 500rpm, particularly preferably less than 400rpm. As the processing time of the ball mill, for example, it can be appropriately adjusted within more than 1 hour and less than 100 hours.
[0070] The calcination in step C is preferably carried out under conditions that can obtain the desired solid electrolyte. Specifically, it is preferably carried out under conditions that can obtain a solid electrolyte containing a crystalline phase having a argyrodite-type crystal structure. From such a viewpoint, it is preferred to carry out the calcination in a hydrogen sulfide gas atmosphere, for example. The calcination temperature is, for example, preferably above 300°C, particularly preferably above 400°C, preferably below 700°C, particularly preferably below 600°C. The calcination time can be appropriately adjusted according to the calcination temperature, for example, preferably above 1 hour and below 10 hours, particularly preferably above 2 hours and below 6 hours.
[0071] It should be noted that the details of the solid electrolyte and its production method are described in, for example, the pamphlet of International Publication No. 2019 / 009228, which is a prior application of the present applicant.
[0072] From the viewpoint of having good lithium ion conductivity, the ratio of the content of the halogen (X) element to the content of the phosphorus (P) element (the content of the halogen (X) element / the content of the phosphorus (P) element) in the solid electrolyte obtained by the present invention, i.e., the so-called sulfide solid electrolyte, is preferably 0.50 or more and 2.1 or less, more preferably 0.80 or more and 2.0 or less, and further preferably 1.2 or more and 1.8 or less in terms of molar ratio.
[0073] When the solid electrolyte obtained by the present invention has a crystal phase of argyrodite-type crystal structure, the solid electrolyte has a composition formula: Li a PS b X c As shown in the formula (wherein X is at least one halogen element, a is greater than 3.0 and less than 6.5, b is greater than 3.5 and less than 5.5, and c is greater than 0.50 and less than 3.0.). In addition, the presence of a crystalline phase containing an argyrodite-type crystal structure can be confirmed, for example, by an X-ray diffraction pattern measured using CuKα1 rays. It should be noted that the details are the same as those described in the International Publication No. 2019 / 009228 pamphlet, so the description is omitted here.
[0074] Example
[0075] The present invention is further described in detail below by way of examples. However, the scope of the present invention is not limited by the examples. Unless otherwise stated, "%" means "mass %".
[0076] [Example 1]
[0077] <1st step>
[0078] As a raw material, powdered Li2SO4·H2O was used. As a carbon-containing solid reducing agent, powdered activated carbon was used. The amount of Li2SO4·H2O used was 86.26 g, and the amount of activated carbon used was 13.74 g. Therefore, the molar ratio of carbon (C) element contained in the activated carbon to 2 moles of oxygen (O) element contained in sulfate ions constituting Li2SO4·H2O, that is, the ratio of C / O2, was 85%.
[0079] Prepare two polyamide cans (volume 500ml), add 43.13g Li2SO4·H2O and 6.87g activated carbon respectively. Add 125g pure water and 600g ZrO2 beads (diameter 5mm) to each can, and cover the can lid. Shake these two cans with a paint shaker for 5 hours to crush and mix the mixed powders in the cans. After crushing and mixing, separate the slurry and beads with a sieve with a mesh of 1mm, and then add the slurry to a 1L reaction container with a SUS jacket, and heat and dry while stirring. Add the obtained mixed powder to a stainless steel container, set the container in a vacuum dryer, and dehydrate the Li2SO4·H2O in the mixed powder at 200°C in a vacuum.
[0080] 30.00 g of the mixed powder was filled into a 100 ml alumina sagger with internal dimensions of 40 mm in length, 130 mm in width, and 24 mm in depth, and placed inside the furnace core tube of a tubular furnace. The furnace core tube was heated to 800°C at a heating rate of 300°C / hour while argon was flowing through it, and heated in an argon atmosphere for 2 hours. The furnace temperature was lowered to room temperature at a cooling rate of 300°C / hour while argon was flowing, and the intermediate product was taken out of the furnace.
[0081] A portion of the intermediate product was taken out, crushed with an agate mortar, and then measured with a powder X-ray diffraction device. The results showed that the I A / I B and I C / I B The values of are shown in the following Table 1. As a powder X-ray diffraction apparatus, SmartLab manufactured by Rigaku Corporation was used. CuKα1 radiation was used as a radiation source.
[0082] After taking out the intermediate product from the above-mentioned furnace, taking out a part of the intermediate product, pulverizing the intermediate product, and performing X-ray diffraction measurement on the intermediate product using a powder X-ray diffraction device were all carried out in a N2 gas atmosphere without being exposed to the air atmosphere.
[0083] <Second step>
[0084] The remaining portion of the intermediate product obtained in the first step was placed in the aforementioned sagger and placed inside the furnace core tube of the tubular furnace. The temperature was raised to 850°C at a heating rate of 300°C / hour while a mixed gas of hydrogen and nitrogen (hydrogen concentration 3.5 vol%) was circulated in the furnace core tube, and the mixture was heated in the aforementioned mixed gas atmosphere for 4 hours. While the aforementioned mixed gas was circulated, the furnace temperature was lowered to room temperature at a cooling rate of 300°C / hour, and the target lithium sulfide was taken out of the furnace.
[0085] A portion of the obtained lithium sulfide was taken out, crushed with an agate mortar, and measured with a powder X-ray diffraction apparatus. The X-ray diffraction pattern showed that C / I B and I D / I B The values are shown in Tables 1 and 2 below.
[0086] It should be noted that taking out the target object from the furnace, taking out a portion of the target object, crushing the target object, and performing X-ray diffraction measurement on the target object using a powder X-ray diffraction device are all carried out in a N2 gas atmosphere without exposure to the atmospheric atmosphere.
[0087] [Example 2]
[0088] In the first step of Example 1, the molar ratio of carbon (C) element contained in activated carbon to 2 mol of oxygen (O) element contained in sulfate ions constituting Li2SO4·H2O, i.e., the ratio C / O2, was changed to 95%. Lithium sulfide was obtained in the same manner as in Example 1 except for this.
[0089] [Example 3]
[0090] In the first step of Example 1, the molar ratio of carbon (C) element contained in activated carbon to 2 mol of oxygen (O) element contained in sulfate ions constituting Li2SO4·H2O, i.e., the ratio C / O2, was changed to 105%. Lithium sulfide was obtained in the same manner as in Example 1 except for this.
[0091] [Example 4]
[0092] In the first step of Example 1, the molar ratio of carbon (C) element contained in activated carbon to 2 mol of oxygen (O) element contained in sulfate ions constituting Li2SO4·H2O, i.e., the ratio C / O2, was changed to 125%. Lithium sulfide was obtained in the same manner as in Example 1 except for this.
[0093] [Example 5]
[0094] In the first step of Example 1, the molar ratio of carbon (C) element contained in the activated carbon to 2 mol of oxygen (O) element contained in the sulfate ion constituting Li2SO4·H2O, i.e., the ratio of C / O2, was changed to 125%. In addition, the heating temperature of the first step was changed to 700° C. Except for these, lithium sulfide was obtained in the same manner as in Example 1.
[0095] [Example 6]
[0096] In the first step of Example 1, the molar ratio of carbon (C) element contained in the activated carbon to 2 mol of oxygen (O) element contained in the sulfate ion constituting Li2SO4·H2O, i.e., the ratio of C / O2, was changed to 125%. In addition, the heating temperature in the second step was changed to 900° C. Except for these, lithium sulfide was obtained in the same manner as in Example 1.
[0097] [Example 7]
[0098] This embodiment is an example in which the third step is performed after the second step is completed.
[0099] In the first step of Example 1, the molar ratio of carbon (C) element contained in the activated carbon to 2 mol of oxygen (O) element contained in the sulfate ion constituting Li2SO4·H2O, i.e., the ratio of C / O2, was changed to 125%. Furthermore, the third step was performed after the second step was completed. Except for this, lithium sulfide was obtained in the same manner as in Example 1.
[0100] In the third step, the lithium sulfide obtained in the second step is placed in the aforementioned sagger inside the furnace core tube of the tubular furnace. The furnace core tube is heated to 500° C. at a heating rate of 300° C. / hour while hydrogen sulfide gas (concentration 100 vol%) is flowing through the furnace core tube, and heated for 1 hour in the hydrogen sulfide gas atmosphere. The furnace temperature is lowered to room temperature at a cooling rate of 300° C. / hour while hydrogen sulfide gas is flowing, and the target lithium sulfide is taken out from the furnace.
[0101] [Example 8]
[0102] This embodiment is an example in which the first step and the second step are performed simultaneously.
[0103] The molar ratio of carbon (C) element contained in the activated carbon to 2 mol of oxygen (O) element contained in the sulfate ions constituting Li2SO4·H2O, that is, the ratio C / O2 was set to 105%.
[0104] 30.00 g of the mixed powder was filled into a 100 ml alumina sagger with internal dimensions of 40 mm in length, 130 mm in width, and 24 mm in depth, and the sagger was placed inside the furnace core tube of a tubular furnace. The temperature was raised to 850° C. at a heating rate of 300° C. / hour while a mixed gas of hydrogen and nitrogen (hydrogen concentration 3.5 vol%) was circulated in the furnace core tube, and the mixture was heated in the mixed gas atmosphere for 4 hours. The furnace temperature was lowered to room temperature at a cooling rate of 300° C. / hour while the mixed gas was circulated, and the target lithium sulfide was taken out from the furnace.
[0105] The same procedure as in Example 1 was carried out except for this.
[0106] [Comparative Example 1]
[0107] This comparative example corresponds to the working example of Patent Document 1 (Japanese Patent Application Laid-Open No. 2013-227180).
[0108] As a raw material, powdered Li2SO4·H2O was used. As a carbon-containing solid reducing agent, powdered activated carbon was used. The amount of Li2SO4·H2O used was 58.48 g, and the amount of activated carbon used was 11.52 g. Therefore, the molar ratio of carbon (C) element contained in the activated carbon to 2 moles of oxygen (O) element contained in sulfate ions constituting Li2SO4·H2O, i.e., the ratio of C / O2, was 105%.
[0109] Prepare two polyamide cans (volume 500ml), add 29.24g Li2SO4·H2O and 5.76g activated carbon respectively. Add 85g n-heptane and 600g ZrO2 beads (diameter 5mm) to the cans, and cover the cans with lids. Shake the cans with a paint shaker for 5 hours to crush and mix the mixed powders in the cans. After crushing and mixing, separate the slurry and beads with a sieve with a mesh of 1mm, and then dry the slurry with a dryer. Put the obtained mixed powder into a stainless steel container, set the container in a vacuum dryer, and dehydrate the Li2SO4·H2O in the mixed powder at 200°C in a vacuum.
[0110] 30.00 g of the mixed powder was filled into a 100 ml alumina sagger with internal dimensions of 40 mm in length, 130 mm in width, and 24 mm in depth, and placed inside the furnace core tube of a tubular furnace. The temperature was raised to 830°C at a heating rate of 300°C / hour while argon gas was flowing through the furnace core tube, and heated in an argon atmosphere for 3 hours. The furnace temperature was lowered to room temperature at a cooling rate of 300°C / hour while argon gas was flowing, and the target object was taken out of the furnace.
[0111] A portion of the obtained target product was taken out, crushed with an agate mortar, and then measured using a powder X-ray diffraction device. The results showed that the I C / I B and I D / I B The values are shown in Tables 1 and 2 below.
[0112] It should be noted that taking out the target object from the furnace, taking out a portion of the target object, crushing the target object, and performing X-ray diffraction measurement on the target object using a powder X-ray diffraction device are all carried out in a N2 gas atmosphere without exposure to the atmospheric atmosphere.
[0113] [Comparative Example 2]
[0114] In Comparative Example 1, the molar ratio of carbon (C) element contained in activated carbon to 2 mol of oxygen (O) element contained in sulfate ions constituting Li2SO4·H2O, namely, the ratio C / O2 was changed to 125%.
[0115] [Comparative Example 3]
[0116] This comparative example corresponds to the working example of Patent Document 2 (Japanese Patent Application Laid-Open No. 2015-74567).
[0117] As a raw material, powdered Li2SO4·H2O was used. As a carbon-containing solid reducing agent, powdered activated carbon was used. The amount of Li2SO4·H2O used was 61.36 g, and the amount of activated carbon used was 8.64 g. Therefore, the molar ratio of carbon (C) element contained in the activated carbon to 2 moles of oxygen (O) element contained in sulfate ions constituting Li2SO4·H2O, that is, the ratio of C / O2, was 75%.
[0118] Prepare two polyamide cans (volume 500ml), add 30.68g Li2SO4·H2O and 4.32g activated carbon respectively. Add 85g n-heptane and 600g ZrO2 beads (diameter 5mm) to the cans, and cover the cans with lids. Shake the cans with a paint shaker for 5 hours to crush and mix the mixed powders in the cans. After crushing and mixing, separate the slurry and beads with a sieve with a mesh of 1mm, and then dry the slurry with a dryer. Put the obtained mixed powder into a stainless steel container, set the container in a vacuum dryer, and dehydrate the Li2SO4·H2O in the mixed powder at 200°C in a vacuum.
[0119] 30.00 g of the mixed powder was filled into a 100 ml graphite sagger with an internal size of 40 mm in length, 130 mm in width, and 24 mm in depth, and placed inside the furnace core tube of a tubular furnace. The furnace core tube was heated to 860°C at a heating rate of 300°C / hour while argon was flowing through it, and heated in an argon atmosphere for 3 hours. The furnace temperature was lowered to room temperature at a cooling rate of 300°C / hour while argon was flowing, and the target object was taken out of the furnace.
[0120] A portion of the obtained target product was taken out, crushed with an agate mortar, and then measured using a powder X-ray diffraction device. The results showed that the I C / I B and I D / I B The values are shown in Table 1 below.
[0121] It should be noted that taking out the target object from the furnace, taking out a portion of the target object, crushing the target object, and performing X-ray diffraction measurement on the target object using a powder X-ray diffraction device are all carried out in a N2 gas atmosphere without exposure to the atmospheric atmosphere.
[0122] [Comparative Example 4]
[0123] In Comparative Example 3, the molar ratio of carbon (C) element contained in activated carbon to 2 mol of oxygen (O) element contained in sulfate ions constituting Li2SO4·H2O, namely, the ratio C / O2 was changed to 85%.
[0124] 〔Evaluation 1〕
[0125] The lithium sulfide obtained in the examples and comparative examples was used as a raw material to produce a sulfide solid electrolyte by the following method. The lithium ion conductivity of the obtained sulfide solid electrolyte was measured by the following method, and the results are shown in Table 1 below.
[0126] <Manufacturing of sulfide solid electrolyte>
[0127] To become Li 5.4 PS 4.4 Cl 0.4 Br 1.2According to the composition of raw materials, lithium sulfide powder, phosphorus pentasulfide powder, lithium chloride powder and lithium bromide powder are weighed respectively to make a total amount of 75g, and the mixed powder is prepared by crushing and mixing with a ball mill for 6 hours. The mixed powder is filled in a graphite sagger, and the sagger is set inside the furnace core tube of a tubular furnace. While hydrogen sulfide gas (concentration 100vol%) is circulated in the furnace core tube at 1.0L / min, the temperature is raised to 500℃ at a heating rate of 200℃ / hour, and heated in this state for 4 hours to obtain a sulfide solid electrolyte. These operations are all carried out in a glove box that has been replaced with fully dry argon (dew point below -60℃).
[0128] <Measurement of lithium ion conductivity>
[0129] The sulfide solid electrolyte was uniaxially pressed at a pressure of 200 MPa, and then cold isostatically pressed (CIP) was performed at a pressure of 200 MPa to produce pellets with a diameter of 10 mm and a thickness of 2 to 5 mm. After the upper and lower surfaces of the pellets were coated with carbon paste as electrodes, they were heat treated at 180°C for 30 minutes to produce samples for measuring lithium ion conductivity. The lithium ion conductivity was measured by the AC impedance method at 25°C. These operations were all carried out in a glove box that was replaced with fully dry argon (dew point below -60°C).
[0130] [Table 1]
[0131]
[0132] [Table 2]
[0133]
[0134] As shown in the results in Tables 1 and 2, the lithium sulfide obtained in each example has a lower content of lithium carbonate and lithium sulfate as impurities than the lithium sulfide of the comparative example. For this reason, the sulfide solid electrolyte using the lithium sulfide obtained in each example as a raw material has a higher lithium ion conductivity than the sulfide solid electrolyte using the lithium sulfide of the comparative example as a raw material.
[0135] Industrial Applicability
[0136] As described above in detail, the method according to the present invention can produce high-purity lithium sulfide.
Claims
1. A method for producing lithium sulfide, comprising: A first step of reducing a raw material containing lithium (Li) and sulfur (S) using a reducing agent containing carbon (C) to obtain an intermediate product; and a second step of reducing the intermediate product using a reducing gas to obtain lithium sulfide, The raw material contains one or more of lithium sulfate, lithium sulfite and lithium thiosulfate. in, The first step is performed as follows: in the X-ray diffraction pattern of the intermediate product measured by an X-ray diffraction device, the intensity of the peak observed at 2θ=25.6°±0.5° is defined as I A , the intensity of the peak observed at 2θ = 27.1° ± 0.5° is defined as I B When the I A Relative to the I B The ratio (I A / I B ) is less than 0.10, and the intensity of the peak observed at 2θ=21.2°±0.5° is set to I C When the I C Relative to the I B The ratio (I C / I B ) is greater than or equal to 0.03 and less than or equal to 0.
09.
2. The method for producing lithium sulfide according to claim 1, wherein: The second step is performed as follows: in the X-ray diffraction pattern of lithium sulfide measured by an X-ray diffractometer, the intensity of the peak observed at 2θ=27.1°±0.5° is defined as I B , the intensity of the peak observed at 2θ = 21.2° ± 0.5° is defined as I C When the I C Relative to the I B The ratio (I C / I B ) is less than 0.
02.
3. The method for producing lithium sulfide according to claim 1 or 2, wherein: The first step is performed in an inert gas atmosphere.
4. The method for producing lithium sulfide according to claim 1 or 2, wherein: The first step is performed under the temperature condition of 700° C. or higher and 850° C. or lower.
5. The method for producing lithium sulfide according to claim 1 or 2, wherein: The second step is performed under the temperature condition of 830°C to 930°C.
6. A method for producing lithium sulfide, comprising the steps of: reducing a raw material containing lithium (Li) element and sulfur (S) element using a reducing agent containing carbon (C) element and a reducing gas to obtain lithium sulfide, The raw material contains lithium sulfate, When 1 mol of carbon element contained in the reducing agent relative to 2 mol of oxygen element contained in the raw material is represented by C / O2, the C / O2 is not less than 0.8 and not more than 1.
3.
7. The method for producing lithium sulfide according to claim 6, wherein: The step is performed under the temperature condition of 830° C. or higher and 870° C. or lower.
8. Lithium sulfide produced by the method according to claim 1 or 6.
9. A method for producing a solid electrolyte, comprising: Step A for obtaining lithium sulfide; Step B of mixing the lithium sulfide, phosphorus pentasulfide and lithium halide to obtain a raw material composition; and Step C of calcining the raw material composition, The step A comprises: a first step of reducing a raw material containing lithium (Li) and sulfur (S) using a reducing agent containing carbon (C) to obtain an intermediate product; and a second step of reducing the intermediate product using a reducing gas to obtain lithium sulfide. The raw material contains one or more of lithium sulfate, lithium sulfite and lithium thiosulfate. in, The first step is performed as follows: in the X-ray diffraction pattern of the intermediate product measured by an X-ray diffraction device, the intensity of the peak observed at 2θ=25.6°±0.5° is defined as I A , the intensity of the peak observed at 2θ = 27.1° ± 0.5° is defined as I B When the I A Relative to the I B The ratio (I A / I B ) is less than 0.10, and the intensity of the peak observed at 2θ=21.2°±0.5° is set to I C When the I C Relative to the I B The ratio (I C / I B ) is greater than or equal to 0.03 and less than or equal to 0.
09.
10. The method for producing a solid electrolyte according to claim 9, wherein: The solid electrolyte includes a crystal phase having an argyrodite-type crystal structure.
